Development of accelerator and brake pedal position comfort ability base on Malaysian population / Davood Hooshyar - Davood , Hooshyar (2019)
Pedal errors mention to the situation when the driver falsely presses the wrong pedal or does not press the pedal at all. A negative outcome of pedal misapplications is a sudden acceleration event, which has been related with crashes. The goal of this dissertation is to identify the factors influencing pedal misapplication through models of driver’s foot movements. Data from 10 subjects were collected by conducting two studies: A parking lot study, and high way study. There were different foot movement seen that could be classified as a direct hit, hesitation, getting out of study scene or doing pedal error. Within the pedal errors, three different sub-categories were seen: wrong pedal, both pedal and miss (no pedal). Using a repeated Logitech Model, pedal errors were indicated to be associated with age-related, situational and experience-based factors. Investigation of the foot movement on a high way study indicated that high speed maneuvers were more likely related with errors as drivers had their foot on the accelerator pedal more often than Brake taking is as a part of game. Further investigation on Parking lot experiment using several Pedal distances and doing functional principal components analysis indicates that the largest contribution to pedal errors were seen in pressing both pedals. Upon summarizing the data, it is observed that highest contributing pedal distance is the smallest one among all 5 levels of pedal distances. This study concludes that 11cm distance is the most suitable as per international Standard and Favorable for Malaysian Population.